Direitos humanos e fundamentais, migração nas fronteiras Brasil e Uruguai : uma análise dos déficits do direito social à saúde da mulher nas cidades gêmeas : Santana do Livramento-BR/Rivera-UR e Chuí-BR/Chuy-UR - Bühring, Marcia Andrea (2013)
The thesis focuses mainly on analyzing the social deficits in relation to human rights and fundamental health of the woman at the border of Brazil and Uruguay, in the Twin Cities, Santana do Livramento (BR) / Rivera (UR) and Chui (BR) / Chuy (UR) in reliance on Article 196 of the Constitution of 1988, which brings the right to health as a state duty and right of all, this human right and fundamental social. Identifies that the phenomenon of human mobility, migrant / displaced / refugees is not new, and in the context of globalization, the issue of vulnerability of these, there is still more evident.For both boundary is redefined as non-place contemporaneously or unusual place, an empty border that separates and unites at the same time, and that has in MERCOSUR, the expectation of the fulfillment of social rights, relegated to the background, and it has also in agreements and adjustments set at the international level, the concrete view of social, among them, highlight the 'Supplementary Agreement for Residence Permit, Work Study and the National Border Brazilians and Uruguayans for Service Delivery Health ', 2008, Decree No. 7.239/10, which enables the traffic and use of health services from both sides. With emphasis on the care provided by the SUS (Unified Health System in Brazil) and SNIS (National Integrated Health, Uruguay) to comprehensive care to women's health, under penalty of social regression.Observed yet to materialize judiciary in ensuring the right to health, with the approach of ADPF 45, which characterizes the ability of the state to implement social rights, as well as analysis of the 'Case of the babies born in Rivera-UR when interdicted the Hospital of Santa Casa in Santana do Livramento-BR in 2009, 'and yet, hiring Uruguayan doctors to work in Brazil - doble attendance sheet at the Border. May prove in the end, research field, with the final report of data from questionnaires applied to women's and Interviews with managers and social actors in related areas.